Elimination of formaldehyde over Cu-Al2O3 catalyst at room temperature - Zhang, Chang-Bin; Shi, Xiao-Yan; Gao, Hong-Wei; He, Hong (Journal of environmental sciences (China), 2005)
Catalytic elimination of formaldehyde (HCHO) was investigated over Cu-Al2O3 catalyst at room temperature. The results indicated that no oxidation of HCHO into CO2 occurs at room temperature, but the adsorption of HCHO occurs on the catalyst surface. With the increase of gas hourly space velocity (GHSV) and inlet HCHO concentration, the time to reach saturation was shortened proportionally. The results of the in situ DRIFTS, Density functional theory calculations and temperature programmed desorption(TPD) showed that HCHO was completely oxidized into HCOOH over Cu-Al2O3 at room temperature. With increasing the temperature in a flow of helium, HCOOH was completely decomposed into CO2 over the catalyst surface, and the deactivated Cu-Al2O3 is regenerated at the same time. In addition, although Cu had no obvious influence on the adsorption of HCHO on Al2O3, Cu dramatically lowered the decomposition temperature of HCOOH into CO2. It was shown that Cu-Al2O3 catalyst had a good ability for the removal of HCHO, and appeared to be promising for its application in destroying HCHO at room temperature.